2015
DOI: 10.1007/s00253-014-6293-3
|View full text |Cite
|
Sign up to set email alerts
|

Response of denitrifying genes coding for nitrite (nirK or nirS) and nitrous oxide (nosZ) reductases to different physico-chemical parameters during agricultural waste composting

Abstract: The present research was performed to clarify the changes of denitrifying genes (nirK, nirS, and nosZ) abundances under different physico-chemical parameters through evaluating the relationships between the genes abundances and parameters during agricultural waste composting. The genes abundances were determined by real-time quantitative PCR (qPCR). The correlations between physico-chemical parameters and denitrifying genes abundances were analysed by regression analysis. qPCR results showed that the nosZ gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Consistent with the first hypothesis prediction, changes in physicochemical parameters shaped different time course patterns of CH 4 - and N 2 O-related functional genes (Gödde and Conrad, 1999; Holtan-hartwig et al, 2002; Kandeler et al, 2006; Zhou et al, 2011; Zhang et al, 2015). Correlation analyses showed that the abundance of pmoA , narG , nirK , and nirS genes shared negative correlations with pile temperature ( r = ∼-0.70, p < 0.05), moisture, TOC, and C/N ratio, and positive correlations with TN ( Figure 4 ), suggesting that changes in interacting physicochemical parameters in the pile shaped the dynamic pattern of the pmoA , narG , nirK , and nirS genes ( Figure 4 ), in line with the results obtained by Hallin et al (2009) showing that nitrate reducers and denitrifiers were closely related to soil TOC, TN, and C/N ratio in a 50-year-old fertilization experiment.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Consistent with the first hypothesis prediction, changes in physicochemical parameters shaped different time course patterns of CH 4 - and N 2 O-related functional genes (Gödde and Conrad, 1999; Holtan-hartwig et al, 2002; Kandeler et al, 2006; Zhou et al, 2011; Zhang et al, 2015). Correlation analyses showed that the abundance of pmoA , narG , nirK , and nirS genes shared negative correlations with pile temperature ( r = ∼-0.70, p < 0.05), moisture, TOC, and C/N ratio, and positive correlations with TN ( Figure 4 ), suggesting that changes in interacting physicochemical parameters in the pile shaped the dynamic pattern of the pmoA , narG , nirK , and nirS genes ( Figure 4 ), in line with the results obtained by Hallin et al (2009) showing that nitrate reducers and denitrifiers were closely related to soil TOC, TN, and C/N ratio in a 50-year-old fertilization experiment.…”
Section: Discussionsupporting
confidence: 76%
“…Similar relationships between methanotrophs abundances and abiotic parameters were found in landfill cover soils (Kumaresan et al, 2009; Lin et al, 2009). Some studies also reported the relationships between denitrifiers and physicochemical parameters, such as correlations of nirK and nirS genes abundance with pile temperature (Zhang et al, 2015), and correlations of narG , nirK and nosZ genes abundance with soil TOC (Kandeler et al, 2006; Zhou et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pH then declined to 8.51 in the final compost. The increase in the pH during the initial stage of composting was due mainly to the release of ammonia and the degradation of organic acids (Li et al, 2014), whereas the decrease in the pH during the later phase was probably caused by the synthesis of phenolic compounds, or the nitrifying process (Zhang et al, 2015). In addition, the pH of Cu2000 was slightly lower than that of the control and Cu200 after 21 days, which may have been related to the adverse effects of Cu on the urease activity (Li et al, 2014), thereby inhibiting the release of ammonia.…”
Section: Resultsmentioning
confidence: 99%